(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Wilson disease is an autosomal recessive disorder of copper metabolism, where excessive copper accumulation occurs in various tissues. Although hepatic and neurological symptoms predominates, it may present with some other unusual features which sometimes confuses clinicians and makes a diagnostic dilemma. We present here an 11 years old boy presented with gradual darkening of whole body over last 2 months and jaundice for 5 month. His clinical features and laboratory parameters were suggestive of Wilson disease. Being one of the common causes of chronic liver disease (CLD) in childhood, Wilson disease may present with some atypical features like darkening of complexion. Bangladesh J Child Health 2018; VOL 42 (1) :43-45